한국산 차나무과 식물에 관한 본초학적 연구 - 정종길; Jong-gil Jeong (大韓本草學會誌, 2017)
Objective : For the purpose of developing Korean herbology of the plants to Theaceae in Korea, the literatures of the successive generations have been thoroughly investigated to prepare this article. Methods : Books and research papers about Herbology which published at home and abroad were examined. Results : A list was made about Theaceae plant which were cultivated or grew naturally in Korea, after investigated the data on domestic and foreign Theaceae plants. Out of those lists, serviceable plants were selected and with those available plants, their distributions were analysed and parts which can be used as medicines were divided into 3 categories such as oriental medicine name, scientific name and non-official name. Theaceae`s properties flavor, channels they use, effects, and toxicity were also noted. Theaceae (grew in Korea) were divided into 6 classes with 12 species. Out of those, 4 classes with 4 species were found serviceable which indicates 33% of all. Out of all 12 species of Theaceae family, Camellia genus and Eurya genus were found 4 species, which were shown the most. Among 4 genus of Theaceae species, medicinal plants were all one species each. Out of all serviceable parts in Theaceae, Folium parts took first place as 4 species. There are toxic, the 2 species and 2 parts survefy said. Conclusion : There were totaled to 6 genera and 12 species in Theaceae in Korea and among them medicinal plants are 4 genera, 4 species, some 33% in total.